Physical training reverses changes in hepatic mitochondrial diameter of Alloxan-induced diabetic rats - Kuga, Gabriel Keine [UNESP]; Gaspar, Rafael Calais; Munoz, Vitor Rosetto; Branco Ramos Nakandakari, Susana Castelo; Breda, Leonardo; Sandoval, Bruna Marina; Caetano, Flavio Henrique [UNESP]; Curiacos de Almeida Leme, Jose Alexandre [UNESP]; Pauli, Jose Rodrigo; Gomes, Ricardo Jose (Inst Israelita Ensino & Pesquisa Albert Einstein, 2018)
Objective: To investigate the effects of physical training on metabolic and morphological parameters of diabetic rats. Methods: Wistar rats were randomized into four groups: sedentary control, trained control, sedentary diabetic and trained diabetic. Diabetes mellitus was induced by Alloxan (35mg/kg) administration for sedentary diabetic and Trained Diabetic Groups. The exercise protocol consisted of swimming with a load of 2.5% of body weight for 60 minutes per day (5 days per week) for the trained control and Trained Diabetic Groups, during 6 weeks. At the end of the experiment, the rats were sacrificed and blood was collected for determinations of serum glucose, insulin, albumin and total protein. Liver samples were extracted for measurements of glycogen, protein, DNA and mitochondrial diameter determination. Results: The sedentary diabetic animals presented decreased body weight, blood insulin, and hepatic glycogen, as well as increased glycemia and mitochondrial diameter. The physical training protocol in diabetic animals was efficient to recovery body weight and liver glycogen, and to decrease the hepatic mitochondrial diameter. Conclusion: Physical training ameliorated hepatic metabolism and promoted important morphologic adaptations as mitochondrial diameter in liver of the diabetic rats.
Keywords: Diabetes mellitus; Exercise; Liver; Wistar, rats